Your step 3 is 1= M(2- 3x)+ N(2+ 3x). By the transitive property, that is the same as 1= 2M- 3Mx+ 2N+ 3Nx.
Combining the terms that include x and those that don't, 1= 3Nx- 3Mx+ (2M+ 2N)= (3N- 3M)x+ (2M+ 2N)= 3(N- M)x+ 2(N+ M)
I cant figure out how the get from step 3 to 4. How are they able to get to that form?
I still get the right answer doing it another way shown in another book but this particular book uses this form and i want to figure it out. Thanks
Your step 3 is 1= M(2- 3x)+ N(2+ 3x). By the transitive property, that is the same as 1= 2M- 3Mx+ 2N+ 3Nx.
Combining the terms that include x and those that don't, 1= 3Nx- 3Mx+ (2M+ 2N)= (3N- 3M)x+ (2M+ 2N)= 3(N- M)x+ 2(N+ M)